Novel Method of FOC to Speed Control in Three-Phase IM under Normal and Faulty Conditions - Mohammad Jannati; Tole Sutikno; Nik Rumzi Nik Idris; Mohd Junaidi Abdul Aziz (Institute of Advanced Engineering and Science, 2015)
This paper proposes a novel method for speed control of three-phase Induction Motor (IM) which can be used for both healthy three-phase IM and three-phase IM under open-phase fault. The proposed fault-tolerant control system is derived from conventional Field-Oriented Control (FOC) algorithm with minor changes on it. The presented drive system is based on using an appropriate transformation matrix for the stator current variables. The presented method in this paper can be also used for speed control of single-phase IMs with two windings. The feasibility of the proposed strategy is verified by simulation results.